The Effect Of Nacl Content Reduces Diarrhea Problems As Well As The Efficacy Of Citrus Aurantifolia In It - Srinatalia Silaen; Cheryl Grace Pratiwi Rumahorbo (Jurnal Penelitian Pendidikan IPA, 2025)
Lime peel contains saponins, flavonoids, alkaloids, tannins, and essential oils that have antibacterial activity. This study aims to explain the relationship between the use of lime peel as a traditional medicine and its bioactivity. Antibacterial activity testing used a Completely Randomized Design (CRD) spray method. The concentrations of lime peel extract used were 12.5, 25, 37.5, and 50%. The positive control used ciprofloxacin and the negative control was 10% DMSO. The results obtained were analyzed by Quasi-Experimental test. The use of plants as traditional medicine is related to their bioactivity and secondary metabolite content. Various researchers have successfully proven the bioactivity of lime peel, namely anticholesterol, antimicrobial, antioxidant, antihypertensive, antiosteoporosis, and anticancer. The concentration and length of contact time are directly proportional to the inhibitory power of CA water against Staphylococcus aureus bacteria. The bioactivity of CA extract as an antimicrobial is influenced by various factors, including the type of microbe, concentration, and contact time. This new study shows that lime peel has the benefit of killing harmful bacteria, such as Escherichia coli, which causes diarrhea. The vitamin C and antioxidants in lime peel are believed to be able to ward off these bacteria.